THE RELATIONSHIP BETWEEN PARENTS' BEHAVIOR AND CARIES IN PRESCHOOL CHILDREN - Welly Anggarani; Nira Ardlina; Ratumas Febrian Orry Sulistianti (Jurnal Medali, 2022)
Background: Caries is a disease of dental hard tissue which is characterized by demineralization and followed by damage to organic matter. The prevalence of dental caries in children in 2018 in Indonesia is still very high, especially at the age of 3-4 years, the prevalence of caries reaches 36.4%, while at the age of 5-9 years it is 54%. The behavior of parents, especially mothers, has an influence on children's oral health, because mothers are role models as well as children's closest figures since birth. There are still many parents who do not know that their behavior affects their child's behavior, and do not consider it important to take care of their child's teeth.Method: This study aims to analyze the relationship between parental behavior on the caries index in children, and also to determine the effect of caries on the quality of life of preschool children. The search for journal literature in this study used 3 databases, namely Google Scholar, Pubmed and NCBI according to keywords, then screened and selected according to inclusion and exclusion criteria.Result: The behavior of parents, especially mothers, will determine the health of children's teeth. In addition, children's behavior also plays a significant role in maintaining the health of their teeth, one of which is in terms of brushing teeth, diet.Conclusion: Parents who have poor behavior in maintaining dental health have a higher risk of developing dental caries than mothers who have a good attitude.